WAYS TO DECREASE INFANT MORTALITY IN A LARGE AGRO INDUSTRIAL REGION IN RUSSIAN NORTH WEST BASED ON A PROGRAMMED GOAL ORIENTED APPROACH (MATERIALS FROM VOLOGDA REGION) - V.I. Orel; Yu.S. Alexandrovich; E.L. Vologdina; E.Yu. Kuznetsova; D.Yu. Batrakov; N.A. Gur'eva; P.V. Kolobukhov ("Paediatrician" Publishers LLC, 2007)
The authors analyze infant mortality situation in a large agroindustrial region to the north west of Russia. Basing on a programmed goal oriented approach and the example of Vologda region, the authors suggest ways to reduce the sickness rate, perinatal, early neonatal and infant mortality, as well as the methods to improve medical aid to early children.Key words: infant mortality, maternity and infant health protection, sickness rate, organization of health services.